THE ROLE OF CIVIC INSTITUTIONS IN THE FORMATION OF INDIVIDUAL’S ENVIRONMENTAL CONSCIOUSNESS - Dinara Arapbayeva (Frontline Social Sciences and History Journal, 2024)
The article highlights the importance of civic institutions in the development of environmental awareness and culture in society. It analyzed the processes of environmental responsibility and consciousness formation in people through non-governmental non-profit organizations, public associations, mass media and local public institutions. Ways to increase environmental culture through environmental education, public initiatives and social actions are also indicated. The article focuses on strengthening public participation in raising an environmentally conscious person and applying the principles of sustainable development to life. This research reveals the importance of cooperation between the state and public organizations in solving environmental problems.